Genetic diversity in wild apple (Malus sp.) populations in Argentina - Calvo, Paula (2010)
In Argentina, wild apple trees are distributed in the western areas of Neuquén province, along the Andean low hillsides. A collection of 23 wild populations was investigated with RAPD primers to evaluate variability and genetic relationships. The data were analyzed by multivariate analysis. A low germplasm variability of 0.115 was estimated with Nei’s genetic diversity index. Cluster and principal coordinate analyses did not reveal distinct geographic patterns or strong grouping among individuals of the same origin, but there was a clear partition between wild and cultivated materials. AMOVA showed the largest level of diversity within populations (57%). A strong human influence seems to have shaped wild apple distribution.